2022
DOI: 10.1111/rec.13800
|View full text |Cite
|
Sign up to set email alerts
|

The acceptable range of variation within the desirable stable state as a measure of restoration success

Abstract: It is standard practice to compare the status of performance indicators between restoration and reference sites to monitor restoration progress and demonstrate restoration success. However, standard methods for defining the reference ecosystem, selecting reference sites, and measuring success are surprisingly lacking. Our study develops these methods based on the acceptable range of variation (ARV) within the desirable stable (reference) state as a measure of restoration success. The method (1) constrains appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…We found that SOC stocks varied substantially among neighboring least-disturbed wetlands with similar vegetation and hydrogeomorphology. In a restoration context, this implies that reference conditions have inherent uncertainty, and that success should be evaluated against the range of natural variability [105]. Although hydrologic metrics explained some variability in SOC stocks, our results highlight the complex and context-dependent relationships between wetland hydrology and ecosystem processes.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We found that SOC stocks varied substantially among neighboring least-disturbed wetlands with similar vegetation and hydrogeomorphology. In a restoration context, this implies that reference conditions have inherent uncertainty, and that success should be evaluated against the range of natural variability [105]. Although hydrologic metrics explained some variability in SOC stocks, our results highlight the complex and context-dependent relationships between wetland hydrology and ecosystem processes.…”
Section: Discussionmentioning
confidence: 81%
“…Constraints on time and funding often put these conditions out of reach for practitioners. With outcomes unpredictable, restoration assessment would benefit from a more rigorous treatment of uncertainty and a greater focus on the natural range of variability [104,105]. For example, strategies like setting targets for groups of wetlands (rather than for individual wetlands) and reducing the precision of targets acknowledge ecosystem dynamism and promote heterogeneity [106,107].…”
Section: High Natural Variability In Wetland Soc Stocksmentioning
confidence: 99%
“…Due to the novel or hybrid nature of rehabilitated ecosystems in the Bowen Basin, it was recommended that the evaluation of rehabilitation should be based on properties found naturally in a broad range of local vegetation types rather than a specific vegetation type (Doley & Audet 2013). Reference sites were used to define the range of variation in the invertebrate diversity levels of the target ecosystem (Oliver et al 2022), remnant woodlands, as a measure of rehabilitation success.…”
Section: Methodsmentioning
confidence: 99%
“…Typical of landforms in this region, the five reference sites were all on gentle slopes of less than 4° slope. As a negative control (Oliver et al 2022), representing the starting vegetation type (i.e., a grassland) and as a counterpoint to the developing wooded vegetation of rehabilitation (Bowie et al 2019), three grassland sites (cleared woodlands) on a similar range of soil types as the woodlands were also selected (P1 on fertile soils, P2 on clay plains and P3 on coarse‐textured soils). Typical of pastures in the Central Queensland region, grassland sites were dominated by the introduced pasture grass, Buffel Grass Cenchrus ciliaris (Eyre et al 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation